Percepção dos residentes de medicina de família e comunidade em relação ao aprendizado de cuidados paliativos - Rodrigues, Paula Ohana (2022)
Advances in medicine and the greater longevity achieved lead to a larger population of elderly people and greater survival with debilitating chronic diseases. As a result, they generate greater demand for palliative care: active holistic care aimed at people with serious illnesses that aim to improve their quality of life. In this perspective, Primary Care and Family Physicians (FP) must be able to provide quality palliative care (PC). Although the PC competences expected from the FP after completing the residency are established, different teaching methodologies are observed in the programs. The aim of the study was to analyze the perception of medicine residents regarding learning about palliative care. The methodology consisted of qualitative research with content analysis of semi-structured interviews carried out with family medicine residents of institutions located in Minas Gerais. It was observed that the programs that have internship in PC, teaching occurs predominantly in an outpatient clinic, for 30 days, mainly through tutored care and case discussion. The residents' perception indicated that the focus is greater on cancer patients, theoretical teaching is poorly structured and the multidisciplinar approach is scarce. In programs that do not have an internship in a specific sector, teaching takes place mainly in the home environment and there are theoretical classes on the subject. However, the workload is not limited, and part of the residents resort to extracurricular courses to acquire skills on the subject. Residents of programs with internships reported feeling more secure in offering PC than those who did not participate in internships in a specific sector. Finally, the residents recommended the presence of an internship in a specific sector that covers the three teaching scenarios (outpatient, home and hospital), with an average duration of two months, that associates different active methodologies of practical and theoretical teaching and has a structured evaluation that matches.